Pembuatan Makanan Tambahan Bubur Singkong Serbuk Marungga Sebagai Upaya Pencegahan Stunting Di Desa Pledo Kecamatan Witihama Kabupaten Flores Timur - Lidya Juiarti Korsini; Yohana Fransiska Medho (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Nutritional problems can occur in any phase of life, starting from the time the child is in the mother's womb until entering old age. One of the nutritional problems that is being hotly discussed is stunting. Stunting is one of the chronic nutritional health problems that is still widespread in Indonesia. One solution to overcome the problem of stunting is to make additional food from marungg powder or moringa leaves where Marungga or moringa has many good benefits for body health, especially in the context of preventing stunting in toddlers. The purpose of this activity is to reduce the increasing number of stunting problems in children in Pledo village by providing additional food in the form of cassava porridge marungga powder. The method used in the process of implementing this activity is to conduct interviews to find out the problems that exist at the location, socialization in the form of stunting crackdowns, making additional food and distributing additional food in the form of cassava porridge marungga powder. The implementation of this service program has obtained very good results for stunting mitigation by providing additional food for Bubur Singkonkong, in addition to making additional food in the form of Cassava Porridge Marungga Powder which is expected to be given or served to children. After this activity, it is hoped that Pledo villagers can use moringa in their daily lives to reduce stunting problems in Pledo village.